Perancangan UI/UX Penerimaan Peserta Didik Baru Berbasis Website Menggunakan Metode User Centered Design - Merrieayu Puspita Hannah; Rizka Nur Kholiza; Kurniawan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
The process of accepting new students is the first process carried out to receive education. The system for accepting new students at Setianegara Sembawa Vocational School is currently still manual. Acceptance of new students starts from the initial registration of students, until the form and proof of registration for accepting new students are still manual. This condition is still applied today, schools often experience errors such as in data input, data processing, and registration files are often damaged and lost. The aim of this research is to help the school overcome existing problems by providing a website-based UI/UX design for accepting new students at Setianegara Vocational School. The design method used by researchers is the user centered design method. User centered design is a method that focuses on the needs of prospective users (users) in the system design stages or process. These needs include comfort and satisfaction when users use the product system that will be designed so that it can be implemented at the next stage. Interviews were conducted with admins, teachers and the general public, solution ideas were collected. Creating user flow and sitemap and UI design in wireframe form. Evaluation is carried out by providing prototype links and questionnaires to potential users. The research results show that website-based PPDB UI/UX design using figma tools with the user centered design method can be carried out at Setianegara Sembawa Vocational School. The results of usability testing show good indicators from a Likert scale calculation of 1-4.